The Public Policy process: A conceptual framework for understanding policy processes and opportunities for influencing policy outcomes - James Origa Otieno (ZBW – Leibniz Information Centre for Economics, 2019)
The ideal policy model is often presented as a neat linear process starting from problem identification, setting policy objectives, creative alternative options, gathering information on options, applying analysis and implementing policy choices. In real life, it isn't always this neat and linear. Real world policy making happens in a world of constraints. Many of these “constraints” eventually are the objectives of policy making. This article presents the murky waters of governance and policy formulation processes in real life. It briefly highlights four analytical lenses for looking at the policy process and offers critical insights into influencing policy outcomes having an understanding of the complex constraints and non-linear dynamics that goes into the process.
Keywords: A31; 330; Policy Process; Political value